THE INFLUENCE OF FOOD QUALITY, BRAND IMAGE AND PRICE ON PURCHASE DECISIONS OF BOGOR'S ASINAN AHAUW TRADITIONAL FOOD - Candra Hidayat; Christin Setiawan; Lilik Hariyanto (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
This study aims to determine the effect of food quality, brand image and price on purchasing decisions for culinary Asinan Ahauw Traditional Food from Bogor. This type of quantitative descriptive research. The population in this study were consumers who bought Asinan Ahauw culinary, Bogor's traditional food, while the sample consisted of 100 respondents. The sampling technique uses accidental sampling. The data collection technique is by distributing questionnaires with a Likert scale from 1 to 5. The results of the study partially show that food quality and brand image have a significant effect on purchasing decisions, while partially they do not have a significant effect on purchasing decisions. the producers of Asinan Ahauw Traditional Food from Bogor to always maintain product quality and build a positive brand image in order to win the competition between Asinan Ahauw producers.